Horbolis L. M. The artistic consept of the life philosophy of the character in the collection «Symphony of Petrykiv forest» by Petro Soroka - Horbolis L. M. (Philological Treatises, 2020)
Lyric trilogy «Symphony of the Petrykiv Forest» is a kind of forest calendar, which contains a wide range of colors, a composition of sounds and smells that together with the emotional-behavioral characteristics of the narrator demonstrate various expressions of his environmental awareness. P. Soroka’s character is attentive, emotional, and touchy, he is a creative person who notices a small, knows how to see, hear and feel some special and unique. In the forest, everything draws narrator’s attention and hearing; character tired of city was impressed and amazed by this place. Living in the forest, P. Soroka’s hero did not lose the mental experience of the sense of nature and communication with it. In the forest, in his opinion, you should come with a calm heart, a peaceful and serene soul, in a joyful mood, because only then you can feel the fullness of life and the happiness that the heart can hold. The escape of P. Soroka’s character, who is a personality, into the forest is caused by the need for something another, unusual, special; it is a flight from the injustice of the world, the imperfect, confused and artificial city space. In the inner organization of the hero-narrator of the lyrical trilogy ancient instincts worked in relation to nature, which is expressed in 1) the need to communicate with nature, 2) respectful attitude to the objects of nature. The hero-narrator appeals to nature as a source of inspiration, he actively assimilates the eco-theory of the moral attitude to the objects of nature, which was produced and tested by his ancestors. He is our contemporary, and his behavior corresponds to the needs of Ukrainian society at the beginning of the XXI century. Contemplating the forest, the hero-narrator produces the philosophy of self-understanding, the self-creation and, importantly, self-esteem. His philosophy of tolerant behavior with the objects of nature is built on ecologically established principles, the ethics of attitude to animate and inanimate nature coordinates and gives meaning to the behavior of the hero, cautiously and politely appeals in the forest. The hero enters organically into the rhythm of life created by the forest and helps to feel confident and cozy. The ecological competence of the hero-narrator of the lyrical trilogy «Symphony of the Petrykiv Forest» becomes the background of the formation of a life philosophy, search of a meaning to life, the comprehension of the essence of being etc. The hero, who loves the environment, makes natural parallels between nature and a man. Spiritual life, moral health, humanistic orientation of behavior, feelings and emotional experiences, the values of the hero-narrator of the lyric trilogy are coordinated by the nature. The trinity, built on the basis of ecological culture, «the desire to be in nature – the ability to handle it – the desire to return to nature» forms the basis of the philosophy of the character’s life.